The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1507/endocrj.ej13-0060
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical characteristics of primary aldosteronism in Japanese patients with type 2 diabetes mellitus and hypertension

Abstract: The prevalence of primary aldosteronism (PA) is around 3-15% in patients with hypertension. Hypertension is a frequent complication of type 2 diabetes mellitus (DM) because of the close etiological relationship between these two diseases. However, the possibility of PA in patients with DM and hypertension is often overlooked and the prevalence of PA in patients with DM and hypertension in Japan is unknown. We enrolled 124 hospitalized patients with both DM and hypertension. PA was diagnosed according to the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 41 publications
4
25
2
Order By: Relevance
“…The present study adds to earlier findings that have shown an association between PA at the clinical level to the metabolic syndrome and various mechanisms between hyperaldosteronism and insulin action . However, in line with earlier studies, clinicians should be alert to considering screening for PA if hypertension (especially resistant) or hypokalaemia exists. Moreover, as earlier studies have shown that high aldosterone levels have been associated with cardiovascular disease, it may also be concluded that high ARR or aldosterone levels do not seem to be strong risk factors for either micro‐ or macrovascular complications in our population of type 2 diabetes patients.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The present study adds to earlier findings that have shown an association between PA at the clinical level to the metabolic syndrome and various mechanisms between hyperaldosteronism and insulin action . However, in line with earlier studies, clinicians should be alert to considering screening for PA if hypertension (especially resistant) or hypokalaemia exists. Moreover, as earlier studies have shown that high aldosterone levels have been associated with cardiovascular disease, it may also be concluded that high ARR or aldosterone levels do not seem to be strong risk factors for either micro‐ or macrovascular complications in our population of type 2 diabetes patients.…”
Section: Discussionsupporting
confidence: 87%
“…PA is considered the most common cause of secondary hypertension . In contrast to the present study, three other studies of PA and type 2 diabetes only included patients with resistant hypertension and found higher prevalence of PA.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…However, the possibility of primary aldosteronism in patients with T2DM and hypertension is often overlooked, in part because hypertension is often attributed to other risk factors commonly encountered in T2DM patients. The prevalence of primary hyperaldosteronism in subjects with T2DM and uncontrolled or resistant hypertension ranges from 11% to 24% in different populations [63][64][65] . This evidence highlights the relevance of screening for hyperaldosteronism in T2DM, especially when there is resistant hypertension, mild or overt hypokalemia or family history or hyperaldosteronism 66,67 .…”
Section: Screen For Mineralocorticoid Excess In Patients With T2dmmentioning
confidence: 99%